2021
DOI: 10.1126/science.abc0269
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB dynamics determine the stimulus specificity of epigenomic reprogramming in macrophages

Abstract: The epigenome of macrophages can be reprogrammed by extracellular cues, but the extent to which different stimuli achieve this is unclear. Nuclear factor κB (NF-κB) is a transcription factor that is activated by all pathogen-associated stimuli and can reprogram the epigenome by activating latent enhancers. However, we show that NF-κB does so only in response to a subset of stimuli. This stimulus specificity depends on the temporal dynamics of NF-κB activity, in particular whether it is oscillatory or non-oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 59 publications
6
115
0
Order By: Relevance
“…In a transient stimulation protocol IκBα-deficient cells show enhanced expression of some genes 15 , as NFκB duration may be discriminated by a slow mRNA decay step or a slow chromatin step 26 . In the persistent stimulation protocol IκBα-deficient cells show NFκB-mediated eviction of many more nucleosomes and establishment of de novo enhancers 27 . However, whether the slowed and diminished NFκB activation observed in IκBα-deficient cells 15 , 24 , 28 affects gene expression has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In a transient stimulation protocol IκBα-deficient cells show enhanced expression of some genes 15 , as NFκB duration may be discriminated by a slow mRNA decay step or a slow chromatin step 26 . In the persistent stimulation protocol IκBα-deficient cells show NFκB-mediated eviction of many more nucleosomes and establishment of de novo enhancers 27 . However, whether the slowed and diminished NFκB activation observed in IκBα-deficient cells 15 , 24 , 28 affects gene expression has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Since A20 mediates negative feedback on TLR and MAVS responses 49 , 50 , this may condition macrophages to undergo an exaggerated response to TLR ligands. A recent study has shown that loss of feedback suppression of NF-κB signaling as would occur with repression of A20, dampens oscillatory NF-κB signaling and sets the stage for increased expression of inflammatory genes as a result of epigenetic reprogramming 51 . Further unraveling of these interconnected pathways could advance the understanding of Sars-Cov-2 pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as it was recently demonstrated for the Bicoid activator Hannon et al ( 2017 ), Dorsal could also have a pioneering activity. Indeed, the Dorsal homolog NF- ,c B has been recently shown to displace nucleosomes ( Cheng et al, 2021 ). To further test the kinetic barrier model, it would be informative to directly perturb the temporal dynamics of nuclear Dorsal concentration to affect transcriptional engagement.…”
Section: Discussionmentioning
confidence: 99%